Measuring the Product Islamic Bank Spin-off in Indonesia: Pros and Cons - Syahdatul Maulida; Aam Slamet Rusydiana (Fara'id and Wealth Management, 2022)
This study aims to look at sentiment towards the development of sharia banking spin off practices in Indonesia. This research is a descriptive qualitative research using sentiment analysis method with the help of SentiStrength software. Of the 43 scientific publications indexed by the Dimension database, it was found that neutral sentiment dominated sentiment related to the spin off policy, namely by 51%, followed by positive sentiment with a percentage of 30%, and negative sentiment by 19%. Based on intertemporal analysis, sentiment developments fluctuate from year to year. The highest peak of sentiment occurred in 2018, namely 7 sentiments which were dominated by 3 positive sentiments.